Development of a pneumatic artificial muscle driven by low pressure and its application to the unplugged powered suit. (2nd November 2017) - Ogawa, Kazunori; Thakur, Chetan; Ikeda, Tomohiro; Tsuji, Toshio; Kurita, Yuichi
Abstract: Assistive suits reduce human muscle effort by improving human motion. However, most assistive suits are bulky, are expensive, need external power sources, and are impractical to carry everywhere. We present the development of the pneumatic gel muscle, which can be actuated by very low air pressure, and its characteristics by comparing with a commercially available artificial muscle. We also discuss the design of an unplugged powered suit for walking assist that unloads the muscle effort using the pneumatic gel muscle, demonstrating that assistive forces can be applied without the use of a compressor or air tanks. We performed experiments to measure characteristics of the pneumatic gel muscle, such as the actuation and applied force, for various pressure ranges. We measured surface EMG of the lower limb with and without an unplugged powered suit to identify the unloading effect of the suit. Abstract :